1989
DOI: 10.1002/jlb.45.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-lnduced Indoleamine 2,3-Dioxygenase Activity in Human Mononuclear Phagocytes

Abstract: Interferon (IFN)-induced tryptophan degradation, catalyzed by indoleamine 2,3-dioxygenase (IDO), has been shown to mediate antimicrobial activity in epithelial cells. IDO activity has also been augmented in peripheral blood mononuclear cells (PBMC) treated with IFN or interleukin-2 (IL-2). The effector cells in this population have now been further characterized. PBMCs were isolated from normal donors, separated into monocyte and lymphocyte populations by plastic adherence, treated with IFN or IL-2, and cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
166
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(185 citation statements)
references
References 20 publications
15
166
0
4
Order By: Relevance
“…In macrophages and human placental cells in culture, IDO expression is regulated by IFN-␥ (27,28). We have previously shown that both IFN-␥ and TNF-␣ are up-regulated in the placenta following L. monocytogenes infection (17).…”
Section: Ifn-␥ But Not Csf-1 Nor Tnf-␣ Regulates Ido Expression In Thmentioning
confidence: 99%
“…In macrophages and human placental cells in culture, IDO expression is regulated by IFN-␥ (27,28). We have previously shown that both IFN-␥ and TNF-␣ are up-regulated in the placenta following L. monocytogenes infection (17).…”
Section: Ifn-␥ But Not Csf-1 Nor Tnf-␣ Regulates Ido Expression In Thmentioning
confidence: 99%
“…While in most investigated in vitro models, IFN-γ is the main inducer of IDO in macrophages, DC, fibroblasts, and microglia [2][3][4][5]46], its expression can also be triggered by lipopolysaccharide (LPS) through an IFN-γ-independent mechanism [47]. The induction of IDO expression without IFN-γ signaling is not dependent on signal transducer and activator of transcription 1α and interferon regulatory factor-1 but requires p38 mitogen-activated protein kinase and nuclear factor-κB [48].…”
Section: Possible Mechanisms Of Ido-mediated Tolerance Inductionmentioning
confidence: 99%
“…The main inducer of IDO, the proinflammatory cytokine IFN-γ, is the key cytokine of encephalitogenic Th1 cells. TNF-α is also secreted by these Th1 cells and acts synergistically with IFN-γ on the induction of IDO in macrophages and microglia [2,6].…”
Section: The Kynurenine Pathway In Eae and Msmentioning
confidence: 99%
See 1 more Smart Citation
“…It leads directly to an opening of the indole ring of tryptophan, thus forming N-formylkynurenine, which rapidly degrades to L-kynurenine [6]. The strongest known inducer is IFN-c, shown in cultured fibroblasts [7], macrophages [8], dendritic cells [9] and many cancer cell lines [10]. The IDO-induced tryptophan depletion, as well as the release of its catabolites in the extracellular environment, arrests activated T lymphocytes in the G1 phase, thereby promoting tolerance [11,12] and leading to apoptosis.…”
Section: Introductionmentioning
confidence: 99%